First record of ubiquitous peaclam Pisidium casertanum (Poli, 1791) (Bivalvia) from the Gölbaşı Lake (Hatay-Turkey) - Sereflısan, Hülya; Başusta, Nuri; Ceviker, Doğan (My University, 2007)
In this study, ubiquitous peaclam Pisidium casertanum (Poli, 1791) was obtained from muddy areas at depths between 1.5 and 2 m in 10 October 2003. For the first time, this species is reported as a new record for Gölbaşı Lake in Hatay (Turkey).
Keywords: Fauna; Pisidium; Pisidium casertanum; new geographic records; Lake Golbasi (Hatay)